Scoparia pentapetala (Plantaginaceae), a new species from the grassland ecosystems of Río de La Plata - Paz Deble, Leonardo; Moreira, Bárbara Pinheiro (Phytotaxa, 2019)
Scoparia is a genus comprising ten species distributed mainly in the grasslands of southern Brazil, Uruguay, Argentina and Paraguay. Based on field surveys, study of nomenclatural types and other specimens, and review of literature we found an interesting new species of Scoparia from southern region of the State of Rio Grande do Sul, Brazil, and Department of Cerro Largo, northeast Uruguay. Described here as S. pentapetala. This work provides a detailed morphological description of the new species, information on geographic distribution, habitat, phenology, conservation status and, discusses the main differences between S. pentapetala and the morphologically most similar species. Illustrations, images and a distribution map are also supplied.